Flow cytometry applications in water treatment, distribution, and reuse: A review. (15th March 2019) - Safford, Hannah R.; Bischel, Heather N.
Abstract: Ensuring safe and effective water treatment, distribution, and reuse requires robust methods for characterizing and monitoring waterborne microbes. Methods widely used today can be limited by low sensitivity, high labor and time requirements, susceptibility to interference from inhibitory compounds, and difficulties in distinguishing between viable and non-viable cells. Flow cytometry (FCM) has recently gained attention as an alternative approach that can overcome many of these challenges. This article critically and systematically reviews for the first time recent literature on applications of FCM in water treatment, distribution, and reuse. In the review, we identify and examine nearly 300 studies published from 2000 to 2018 that illustrate the benefits and challenges of using FCM for assessing source-water quality and impacts of treatment-plant discharge on receiving waters, wastewater treatment, drinking water treatment, and drinking water distribution. We then discuss options for combining FCM with other indicators of water quality and address several topics that cut across nearly all applications reviewed. Finally, we identify priority areas in which more work is needed to realize the full potential of this approach. These include optimizing protocols for FCM-based analysis of waterborne viruses, optimizing protocols for specifically detecting target pathogens, automating sample handling and preparation to enable real-time FCM, developing computational tools to assist data analysis, and improving standards for instrumentation, methods, and reporting requirements. We conclude that while more work is needed to realize the full potential of FCM in water treatment, distribution, and reuse, substantial progress has been made over the past two decades. There is now a sufficiently large body of research documenting successful applications of FCM that the approach could reasonably and realistically see widespread adoption as a routine method for water quality assessment. Graphical abstract: Image 1 Highlights: Flow cytometry (FCM) is an accepted tool to characterize microbial water quality. Nearly 300 studies between 2000 and 2018 applied FCM to water quality assessment. Research illustrates the value of FCM in water treatment, distribution, and reuse. FCM-based monitoring can facilitate assessment of treatments for potable reuse. Automated and standardized FCM data collection and analysis methods are needed.